Respuesta :
[tex]f(x)=x^{2}-2x-3 \\ \\ \Delta=(-2)^{2}-4*1*(-3)=4+12=16 \\ \\ a= \frac{2}{2}=1 \\ \\ b= \frac{-16}{4}=-4 \\ \\ x^{2}-2x-3=(x-1)^{2}-4=(x-1)^{2}=4 [/tex]
\\\ Ben
\\\ Ben
Answer:
The correct option is 4.
Step-by-step explanation:
The given equation is
[tex]x^2-2x-3=0[/tex]
If an expression is [tex]x^2+bx[/tex], then to make it perfect sqaure add [tex](\frac{b}{2})^2[/tex].
[tex](x^2-2x)-3=0[/tex]
Here b=-2,to make the perfect square we need to add [tex](\frac{-2}{2})^2[/tex],i.e, 1.
[tex](x^2-2x+1)-1-3=0[/tex]
[tex](x-1)^2-4=0[/tex] [tex][\because (a-b)^2=a^2-2ab+b^2][/tex]
Add 4 on both the sides.
[tex](x-1)^2-4+4=0+4[/tex]
[tex](x-1)^2=4[/tex]
Therefore the correct option is 4.